2006
DOI: 10.1177/0047117806069410
|View full text |Cite
|
Sign up to set email alerts
|

Discourses in Transition: Re-Imagining Women's Security

Abstract: This article employs data gathered in Lebanon, Northern Ireland and South Africa as part of a project entitled 'Re-Imagining Women's Security and Participation in Post-Confl ict Societies'. It refl ects on three different 'imaginings' of security -the state security discourse, the human security discourse and a gendered security approach -with the aim of showing that security discourses are currently undergoing a process of transition which parallels that taking place in post-confl ict societies around the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Men with a remaining traditional image of manhood are confronted with a "new women's world" when returning to their families after imprisonment. This often leads to contentious male-female relationships, in many cases to domestic violence and marriage breakdown; these contentions in the private realm can further be a contributing factor to an increase in self-harm, evident in suicides, alcoholism, and drug abuse Hamber et al, 2006). The focus on the regulation of ethnic distinctions in the public peace process does not provide sufficient space to address post-agreement issues like the crisis partnerships, which occurs in the private realm.…”
Section: Intersecting Boundary Processes In Peace Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Men with a remaining traditional image of manhood are confronted with a "new women's world" when returning to their families after imprisonment. This often leads to contentious male-female relationships, in many cases to domestic violence and marriage breakdown; these contentions in the private realm can further be a contributing factor to an increase in self-harm, evident in suicides, alcoholism, and drug abuse Hamber et al, 2006). The focus on the regulation of ethnic distinctions in the public peace process does not provide sufficient space to address post-agreement issues like the crisis partnerships, which occurs in the private realm.…”
Section: Intersecting Boundary Processes In Peace Processesmentioning
confidence: 99%
“…This results in different outcomes of the mobilization and demobilization process at the micro level; first, contention in intimate partnerships, visible in reports about an increase in domestic violence (PSNI, 2012), often connected to an increase in alcoholism in Northern Ireland linked to the lack of reconciling "violent conflict masculinities" Hamber et al, 2006). Second, we can observe in both cases a tendency toward an increasing distance between men and women, evident in many reported martial breakdowns in Northern Ireland and in Chiapas and the decisions of some women not to get married.…”
Section: (Dis-) Connecting Different Dimensions: the Private Realm Bementioning
confidence: 99%
“…Literature in Northern Ireland and South Africa indicates that men in both countries feel that new protections toward women allow women to benefit unfairly (Geisler, 2004;Ginwala, 1998Ginwala, /2005Northern Ireland Office of Statistics and Research Branch, 2006;OFMDFM, 2012). Despite evidence to the contrary (Antonopolous, 2007;ISS, 1999;Unterhalter, 2005;Vetten, 2002;Vogelman, 2000;Women's Aid, 2011;Women's Net, 2012), men tend to feel that women surpass them educationally and in employment (Bairner, 1999;Hamber, 2010;Shirlow, 1997;Xaba, 2000;Vetton 2000;Hamber et al, 2006;Harland 2011).…”
Section: Background Of Violencementioning
confidence: 99%
“…Moreover, by privileging elite constructions of security (Buzan et al., 1998, p. 29; Wæver, 1995, pp. 56–57), this approach neglects the potential for the ‘bottom‐up’ and ‘people‐centred’ perspectives emphasised by human security to ‘re‐imagine security’ in counter‐hegemonic ways (Hamber et al., 2006; Hoogensen and Stuvøy, 2006; more broadly, see Booth, 2005, p. 266). In the context of post‐conflict peace‐building, for example, ethnographic studies have indicated the ways in which ‘listening’ to the security concerns of women and other politically marginalised groups reveals ‘the inadequacies of institutionalised security approaches to meet [people's] holistic security needs’ and thus strengthens political demands for social transformation (Hamber et al., 2006, p. 495; see also Krause and Jütersonke, 2005, p. 460).…”
Section: The Politics Of Securitymentioning
confidence: 99%